Motion Control of Three-Rotor Unmanned Underwater Vehicle - Bal, Cafer; Korkmaz, Deniz; Bingol, Mustafa Can (Springer International Publishing Ag, 2018)
This paper presents the design of a three-rotor Unmanned Underwater Vehicle (UUV) and generating nonlinear mathematical model. The main propose of this design is to adapt to the UUV effective propellers. For this purpose, three-rotor model is aligned to the Center of Gravity (CoG) and UUV can move in three dimensional space. The derived mathematical model includes the kinematics, dynamics and hydrodynamics effects acting on the body. In order to achieve 6-DoF motion control, three-layered control structure is designed and generalized linear/angular positions and velocities are examined. In addition, three dimensional circular trajectory tracking is performed to achieve effective motion responses.
12th International Conference on Mechatronics -- SEP 06-08, 2017 -- Brno, CZECH REPUBLIC
Keywords: Underwater vehicle; Dynamic modeling; Motion control; Trajectory tracking